CONSERVATIVE IDEOLOGY OF INDONESIAN MUSLIMS: THE ROLE OF EPISTEMIC MOTIVATION, AUTHORITARIANISM AND ISLAMIC TOTALISM - Istiqomah Istiqomah; Bagus Takwin (Psikis : Jurnal Psikologi Islami, 2020)
This research proves that religiosity (Islamic totalism) is a predictor of conservative ideology, as is the need for cognitive closure and right wing authoritarian which has been proven as a psychological variable that affects conservative ideology. The ideology of conservatism emphasizes on the tendency to preserve what is already established, resist change and maintain existing orders whether social, economic, legal, religious, political, or cultural (Jost, Glaser, Kruglanski, & Sulloway, 2003). This research utilized a quantitative survey method. Participants of this study were 528 college students from Jakarta with multiple regression analysis. The results obtained are 1) Islamic totalism, cognitive closure and right wing authoritarian are social and economic conservatism predictors; 2) only Islamic totalism is a religious conservatism predictor; 3) Islamic totalism has the greatest influence on social, economic and religious conservatives.